2021
DOI: 10.1038/s41467-021-24008-9
|View full text |Cite
|
Sign up to set email alerts
|

A global analysis of extreme coastal water levels with implications for potential coastal overtopping

Abstract: Climate change and anthropogenic pressures are widely expected to exacerbate coastal hazards such as episodic coastal flooding. This study presents global-scale potential coastal overtopping estimates, which account for not only the effects of sea level rise and storm surge, but also for wave runup at exposed open coasts. Here we find that the globally aggregated annual overtopping hours have increased by almost 50% over the last two decades. A first-pass future assessment indicates that globally aggregated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 135 publications
(74 citation statements)
references
References 85 publications
1
73
0
Order By: Relevance
“…Coastal storms erode sandy beaches and dunes (Vellinga, 1982;McCall et al, 2010;Castelle et al, 2015;Masselink et al, 2016;Harley et al, 2017) with direct impacts on coastal communities through damages to developments and infrastructure (Jongejan et al, 2016;Ballesteros et al, 2018), reduction of beach's touristic and recreational value (Monioudi et al, 2017;Toimil et al, 2018), and disturbance of coastal ecosystems (Mehvar et al, 2018;Paprotny et al, 2021). Moreover, the beach and dune system forms the first line of defense against coastal flooding, and their weakening or breaching can worsen the hinterland's susceptibility to flooding (Grzegorzewski et al, 2011;Keijsers et al, 2015;van Dongeren et al, 2018;Almar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Coastal storms erode sandy beaches and dunes (Vellinga, 1982;McCall et al, 2010;Castelle et al, 2015;Masselink et al, 2016;Harley et al, 2017) with direct impacts on coastal communities through damages to developments and infrastructure (Jongejan et al, 2016;Ballesteros et al, 2018), reduction of beach's touristic and recreational value (Monioudi et al, 2017;Toimil et al, 2018), and disturbance of coastal ecosystems (Mehvar et al, 2018;Paprotny et al, 2021). Moreover, the beach and dune system forms the first line of defense against coastal flooding, and their weakening or breaching can worsen the hinterland's susceptibility to flooding (Grzegorzewski et al, 2011;Keijsers et al, 2015;van Dongeren et al, 2018;Almar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Ranasinghe et al [45] and Anderson et al [46] observed shoreline rotation at embayed beaches, and Trombetta et al [47] observed an alongshore sediment drift reversal with large consequences for coastal zone management and infrastructures. These remote swells can also drive dramatic overtopping [6] even at storm-free areas, such as in the Gulf of Guinea [1,48], facing the South Atlantic storm track, and in the Pacific due to distant tropical cyclones [17,[49][50][51].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Wind-generated ocean surface waves represent the principal driver of open littoral vulnerability over a wide range of scales including long interannual timescales [1]. In particular, coastal breaking waves have been shown to contribute significantly to extreme coastal water-level episodes and associated flooding and erosion [2][3][4][5][6], therefore strongly impacting littoral socio-economic systems and human activities, e.g., coastal infrastructures' maneuverability [7], energy resources [8], marine/mangrove ecosystems [9,10], water quality [11,12], aquaculture, and oil industries [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…These risks include permanent and/or short periods of submersion, disruption of coastal ecosystem functioning and destruction of these ecosystems, soil and aquifer salinization, and modification of natural drainage systems (IPCC, 2019). By 2100 extreme SLR events will become frequent, regardless of the selected emission scenario (IPCC, 2019) and more regions are projected to become exposed to coastal flooding and inundation (Almar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%